The Dimension of Sufism in Muhammadiyah: A study of KH. Ahmad Dahlan’s Thought - DH, Achmad Zuhdi (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study delves into the role of Sufism in KH. Ahmad Dahlan’s thoughts and how it shaped the spiritual core of the Muhammadiyah movement. Although Muhammadiyah is widely recognized as a modernist Islamic reform movement focused on rational interpretation and purification of religious practice, it is often perceived to overlook spiritual traditions like Sufism. This research adopts a qualitative method with a historical-hermeneutic framework, analyzing primary sources including KH. Ahmad Dahlan’s biographies, early Muhammadiyah records, and testimonies from his disciples and contemporaries. Discourse analysis is also applied to uncover the manifestation of Sufi principles within Muhammadiyah’s foundational activities such as education, preaching, and moral guidance. The study finds that KH. Ahmad Dahlan incorporated key Sunni Sufi values—especially soul purification (tazkiyatun nafs), sincerity, and ethical development—into the organization’s educational and social engagement. These insights confirm that Dahlan’s renewal (tajdid) initiative did not dismiss Sufism, but instead reformulated it within a moral and spiritual Islamic modernism.